Colorectal cancer screening: 20 years of development and recent progress - Zavoral, Miroslav (Baishideng Publishing Group Co., Limited, 2014)
Colorectal cancer (CRC) is the second most common cancer in Europe and its incidence is steadily increasing. This trend could be reversed through timely secondary prevention (screening). In the last twenty years, CRC screening programs across Europe have experienced considerable improvements (fecal occult blood testing; transition from opportunistic to population based program settings). The Czech Republic is a typical example of a country with a long history of nationwide CRC screening programs in the face of very high CRC incidence and mortality rates. Each year, approximately 8000 people are diagnosed with CRC and some 4000 die from this malignancy. Twenty years ago, the first pilot studies on CRC screening led to the introduction of the opportunistic Czech National Colorectal Cancer Screening Program in 2000. Originally, this program was based on the guaiac fecal occult blood test (FOBT) offered by general practitioners, followed by colonoscopy in cases of FOBT positivity. The program has continuously evolved, namely with the implementation of immunochemical FOBTs and screening colonoscopy, as well as the involvement of gynecologists. Since the establishment of the Czech CRC Screening Registry in 2006, 2405850 FOBTs have been performed and 104565 preventive colonoscopies recorded within the screening program. The overall program expanded to cover 25.0% of the target population by 2011. However, stagnation in the annual number of performed FOBTs lately has led to switching to the option of a population-based program with personal invitation, which is currently being prepared.